THE ORIGIN OF PHRASEOLOGICAL UNITS (World Bulletin of Social Sciences, 2024)
In this article is discussed opinions about phraseology, the origin of phraseology, phraseogical unities and phraseological fusions. It is also focused on semantic and structure of phraseological units.